Is there a proximal shift in the distribution of colorectal adenomas? - Oliveira, AM (2016)
Submitted by arminda sustelo (arminda.sustelo@hff.min-saude.pt) on 2016-03-29T15:55:38Z No. of bitstreams: 1 United European Gastroenterol J. 2015 Aug, 3(4) 353-7.pdf: 290579 bytes, checksum: 673259796bd956a9289fb8a3c6f27383 (MD5)